THE INFLUENCE OF CORPORATE GOVERNANCE AND PROFITABILITY ON THE SOLVENCY ACHIEVEMENT OF THE INSURANCE INDUSTRY - Indira Januarti; Thifal Suci Khairunnisa (Universitas Katolik Indonesia Atma Jaya, 2022)
This study aims to discuss the effect of corporate governance and profitability on the solvability rate of general insurance companies and life insurances companies in Indonesia. The variables used in this study are the dependent variable (solvability rate) and independent variable (board of commissioners, independent commissioners, board of directors, and profitability). The population in this study is general insurance companies and life insurance companies listed on the Insurance Directory of Otoritas Jasa Keuangan in the period 2017–2019. Based on criteria, samples obtained were 213 for the three years obtained (2017–2019). The analytical method used in this study is multiple regression with SmartPLS software. This study indicates that board of commissioners and profitability have a significant positive effect on the solvability rate